Fotossíntese, relações hídricas, estado nutricional e avaliação de caracteres secundários da produção em dois cultivares jovens de seringueira em São José do Rio Preto,SP - Cavalcante, Juliane Ribeiro (2003)
This study was accomplished with two young cultivate of rubber tree, Hevea brasiliensis (Willd. ex Adr. of Juss.) Müell. Arg.], RRIM 600 and Fx 3864. This work obtained information comparatively on cultivating Fx 3864 to RRIM 600 already established in the from São Paulo Occidental Plateau, through the gas exchange, osmotic and leaf water potential, status nutritional and evaluation of the secondary characters of the production. In that way, it was aimed at to indicate a new one to cultivate (Fx 3864) potentially alternative for the plantation in commercial scale in the region of São José do Rio Preto, SP, and to contribute in the reduction of the improvement cycle and selection of new cultivate. The plants were maintained in field conditions in argissolo in the experimental area of Zoology Department and Botany of UNESP/IBILCE in São José do Rio Preto, SP. During the period of 2001 and 2003, when the plants between 04 and 27 months of age, daily measures of the gas exchange were accomplished, answer curves to the light, measures of osmotic potential; evaluation of the height of the plant (HP), perimeter of the stem (PS), number of releases (N R), leaf area (LA), diameter of the cup in the line and in the among-line (DC-L, DC-AL), bark thickness (BT), mass dries of the stem and of the leaf (MDS, MDL) and specific mass to foliate (SMF) and status nutritional of the plants. The values of the gas exchange in leaf had shown a decrease in phtosynthesis of 32 and 22%, transpiration of 44 and 38% and stomatal conductance of 29 and 17% for RRIM 600 and Fx 3864, respectively. The reduction in the stomatal conductance and in the transpiration rate, observed for both cultivates them, had indicated a preventive behavior to the dehydration of the tissue in the dry period. Through the water status, an osmotic adjustment was observed in both cultivates them in the dry period, making possible the operation of the rate photosynthesis. With relation to secondary characters of the production cultivating RRIM 600 was distinguished in height in relation to Fx 3864. However, Fx 3864 presented DC-L and DC-AL larger. The BT was similar among them you cultivate during the whole study period. To cultivate them from the 2° year of experiment had not presented significant differences in the values of PS, N R and LA. Values of macro and micronutrientes met inside of the strip considered appropriate for rubber tree, evidencing that in the argissolo conditions the values of those nutrients are enough for the rubber tree to manifest her full productive potential. Considering the group of physiologic and environmental characters analyzed, the performance of cultivating Fx 3864 was equivalent to the of RRIM 600 in the first two years of life.